0087 Feasibility of examining component-specific effects of yogic breathing on self-report sleep metrics: A three-arm pilot RCT. (25th May 2022) - Vazquez, Michael; Buraks, Olivia; Haack, Monika; Mullington, Janet; Yang, Huan; Goldstein, Michael
Abstract: Introduction: Mind-body interventions (MBIs) continue to receive widespread interest for improving sleep disturbances. This study investigated the feasibility of using an automated electronic survey system in REDCap in the context of a fully remote clinical trial study to produce detailed measures of participant adherence, daily sleep quality, and associations with physiological outcomes captured by wearable devices. Methods: Eighteen healthy participants (age 18-30 yrs, 12 female) were randomized to one of three 8-week long interventions: slow-paced breathing (SPB, N=5, 24.6 ± 2.1 years, 4 female), mindfulness (M, N=6, 23.7 ± 3.7 years, 4 female), or yogic breathing (SPB+M, N=7, 24.3 ± 3.1 years). Participants completed two weeks of daily sleep logs along with the Pittsburgh Sleep Quality Index (PSQI) prior to a virtual laboratory visit, which consisted of a 60-min intervention-specific training, including a 20-min guided practice, and subsequent tasks including experimental stress induction. Participants were then instructed to repeat their assigned intervention practice daily, selecting either the same or a similar guided audio as their initial training. After an initial video check-in appointment, participants received regular visual feedback of their data and completed weekly check-ins with the study team to improve adherence. At the end of the intervention period, participants again completed daily sleep logs and the PSQI, in addition to other outcome measures and a virtual laboratory visit. Data were analyzed using linear mixed models. Results: Sleep log adherence was over 90% in all three groups. The groups were successfully distinguishable based on HRV-derived breathing and mindfulness ratings. For the SBP+M group only, there was a trend of reduced sleep onset latency (SOL, p=.093) and a significant increase in sleep efficiency (SE, p=.025). There were no significant changes in PSQI or other sleep log measures. More detailed analysis of timecourse across these measures is ongoing. Conclusion: These findings support feasibility for a fully remote, semi-automated clinical trial study assessing component-specific effects of these MBIs on sleep in generally healthy young adults. Research evaluating MBIs for sleep in both clinical and nonclinical populations would benefit from similar study designs to examine intervention-specific components while increasing both scalability and quality control. Support (If Any): Pilot Research Grant, Osher Center for Integrative Medicine of Harvard Medical School and Brigham & Women's Hospital; National Institutes of Health (5T32HL007901-22)